1996
DOI: 10.1002/mrm.1910360416
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity‐enhanced echo‐planar MRI at 1.5T using a 5 × 5 mesh dome resonator

Abstract: In this work a 5 x 5 mesh dome resonator that has been optimized for functional brain imaging is presented. The resonator was reduced in length and diameter compared with previous versions to reduce sample losses, thus enhancing the signal-to-noise ratio of the acquired data. In addition, a 5 x 5 mesh design was employed, which offered improved axial homogeneity over an earlier 3 x 3 mesh version. The new resonator exhibited high sensitivity and good homogeneity over the brain volume, permitting analysis of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The phosphorus mode B 1 maps generated from 2D-CSI phantom studies were in general agreement with theoretical predictions. This was expected based on previous results for this mode observed with proton-tuned 3 ϫ 3 and 5 ϫ 5 mesh dome resonators (5,6). An axial 17 cm diameter slice through Phantom 2 demonstrated a variation of less than 5% in the phosphorus B 1 intensity over the cross section.…”
Section: Clinical Performance Of the Dual-tuned Resonatorsupporting
confidence: 83%
See 2 more Smart Citations
“…The phosphorus mode B 1 maps generated from 2D-CSI phantom studies were in general agreement with theoretical predictions. This was expected based on previous results for this mode observed with proton-tuned 3 ϫ 3 and 5 ϫ 5 mesh dome resonators (5,6). An axial 17 cm diameter slice through Phantom 2 demonstrated a variation of less than 5% in the phosphorus B 1 intensity over the cross section.…”
Section: Clinical Performance Of the Dual-tuned Resonatorsupporting
confidence: 83%
“…Several cylindrical dual-tuned resonator designs have been presented that permit consecutive proton imaging and shimming as well as phosphorus spectroscopic acquisition (1)(2)(3). The goal of this work was to generate a dual-tuned brain resonator based on dome-shaped two-dimensional (2D) ladder network designs that have been used successfully in proton studies (4)(5)(6). Unlike cylindrical resonators, whose sensitivity decreases at both ends relative to the center, the dome structure maintains sensitivity at the closed ''dome'' end.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Professor Lee’s initial research into functional neuroimaging was conducted during his clinical training at Cornell University Medical College and Memorial Sloan-Kettering Cancer Center. 24 He and colleagues reported intriguing fMRI findings of distinct cortical areas associated with native and second languages in 12 bilingual subjects at various stages of second-language acquisition. 25 They concluded that the processing of two languages tends to occur in spatially distinct regions of Broca’s area when the second language was acquired late in life rather than during early childhood, whereas Wernicke’s area showed little or no separation of activity regardless of the age of acquisition.…”
Section: Functional Neuroimaging Studiesmentioning
confidence: 99%
“…In this work the network's geometry and desired currents are assumed to be determined by independent design choices or optimizations. We present a general method to determine the capacitance values required to produce a desired modal structure in circuits such as two‐dimensional (2D) ladder networks or cyclic structures such as the birdcage coil including variants such as the dome resonator , the transverse electromagnetic (TEM) coil , ring resonator , and magnetron .…”
Section: Introductionmentioning
confidence: 99%